2003
DOI: 10.2174/0929867033457610
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tridentate Iron Chelators: From Desferrithiocin to ICL670

Abstract: Successful treatment of beta-thalassemia requires two key elements: blood transfusion and iron chelation. Regular blood transfusions considerably expand the lifespan of patients, however, without the removal of the consequential accumulation of body iron, few patients live beyond their second decade. In 1963, the introduction of desferrioxamine (DFO), a hexadentate chelator, marked a breakthrough in the treatment of beta-thalassemia. DFO significantly reduces body iron burden and iron-related morbidity and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
115
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 0 publications
1
115
0
1
Order By: Relevance
“…The main toxic effects described were changes of renal tubular cells. The nephrotoxicity was regarded to be caused by decompartmentalization of chelated iron and had been observed in animals that were not heavily iron-overloaded [15]. Based on these observations, a creatinine clearance of <60 mL/ min was determined as an exclusion criterion for deferasirox treatment as recommended by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main toxic effects described were changes of renal tubular cells. The nephrotoxicity was regarded to be caused by decompartmentalization of chelated iron and had been observed in animals that were not heavily iron-overloaded [15]. Based on these observations, a creatinine clearance of <60 mL/ min was determined as an exclusion criterion for deferasirox treatment as recommended by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…Deferasirox binds iron in a 2:1 ratio before being excreted primarily in the bile [15]. A series of studies have demonstrated its efficacy and safety in patients with thalassemia major in a daily dose ranging between 20 and 30 mg/kg [12,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…22 It is orally bioavailable and its terminal end half-life (t1/2) is somewhere around 8 and 16 hours, taking into consideration once-every day organization. Digestion system and end of deferasirox and the iron chelate (Fe-[deferasirox]2) is basically by glucuronidation took after by hepatobiliary discharge into the defecation.…”
mentioning
confidence: 99%
“…Actually, Deferasirox is available in 90 nations. 34 Deferasirox, a N-substituted bis-hydroxyphenyltriazoles compound, belongs to a new class of tridentate iron chelators. It was selected among more than 700 molecules because it is orally administrable and it gave the best therapeutic results.…”
mentioning
confidence: 99%
“…It was selected among more than 700 molecules because it is orally administrable and it gave the best therapeutic results. 34,35 Two molecules of Deferasirox are able to generate a stable complex with one molecule of iron. Its half life (t1/2) is between 8 and 16 hours, allowing a once-daily administration.…”
mentioning
confidence: 99%